Ubiquitin E3 ligase MARCH7 promotes ovarian tumor growth - Hu, Jianguo (Oncotarget, 2015)
Ubiquitin E3 ligase MARCH7 is involved in T cell proliferation and neuronal development. We found that expression of MARCH7 was higher in ovarian cancer tissues than normal ovarian tissues. Silencing MARCH7 decreased cell proliferation, migration, and invasion. Ectopic expression of MARCH7 increased cell proliferation, migration and invasion. Silencing MARCH7 prevented ovarian cancer growth in mice. Silencing MARCH7 inhibited NFkB and Wnt/β-catenin pathway. In agreement, ectopically expressed MARCH7 activated NFkB and Wnt/β-catenin pathways. Finally, MARCH7 was regulated by miR-101. Thus, MARCH7 is oncogenic and a potential target (oncotarget) for ovarian cancer therapy.